The Role of Personality in Prediction of Satisfaction With Life in Recreational Athletes During the First Wave of Pandemic Covid-19 - Živković, Danijela; Nedeljković, Jasmina; Veljković, Bojan; Đošić, Anđela; Bojanić, Željka; Bratić, Milovan; Pantelić, Saša (Frontiers in Psychology, 2022)
The aim of this research is to contribute to the understanding of the concept of satisfaction with life by determining the relationship between personality traits and the subjective experience of satisfaction with life in students – recreational athletes. This research is based on the biological theory of personality by Hans Eysenck and it attempts to offer explanations of a possible change in satisfaction with life in the period of great social deprivation caused by the Covid-19 pandemic. The sample of subjects consisted of 120 undergraduate students (N=120) of all years and both sexes, 55 (45.8%) males and 65 (54.2%) females, at the Faculty of Sport and Physical Education, the University of Nis. The average age of the subjects was 23.63 years (SD=2.070). Eysenck’s personality questionnaire (Eysenck Personality Questionnaire, EPQ: Eysenck, Eysenck, & Barrtett, 1985, adapted and translated by Šipka, 1985) was used for the operationalization of personality structure. The SWLS scale (Satisfaction With Life Scale, Diener et. al., 1985) was used for estimating satisfaction with life. A significant regression model, which explains 11% of variance in the subjective experience of satisfaction with life in recreational athletes, was obtained. In the model, extraversion stands out as a significant predictor from the group of personality traits (β= .279). Neuroticism (β= -.160) and psychoticism (β= -.122) did not prove to be significant predictors of satisfaction with life in the structural model regardless of there being a significant negative correlation between neuroticism and satisfaction with life. The more extraverted participants had a keener subjective sense of satisfaction with life.